The Role of Digital Marketing in Enhancing the Goat Farming Economy: A Case Study of CV. Prima Mandiri Abadi - Hussam, Haidir; Rombe, Elimawaty; Parani, Syamsul Bahri Daeng; Palawa, Muh Riswandi (Yayasan Riset dan Pengembangan Intelektual, 2025)
Sales through social media, supported by digital marketing, enable entrepreneurs to introduce their products more effectively. CV. Prima Mandiri Abadi, a company engaged in goat farming, has adopted digital marketing strategies to enhance its sales performance. This study employs a descriptive method, with data collected through surveys and in-depth interviews, utilizing a qualitative research approach. The sales of Ettawa (PE) goats from 2021 to 2023 showed fluctuations. In 2022, PE goat sales peaked at 96 heads, while the lowest sales were recorded in 2023 with 67 heads. In contrast, sales of local goats demonstrated significant growth in 2023, reaching 396 heads. Digital marketing has proven to be a key driver for CV. Prima Mandiri Abadi in increasing goat sales by leveraging various digital platforms, including WhatsApp, Facebook, Instagram, TikTok, and E-Catalogs. These findings highlight the potential of digital marketing in supporting economic growth within the livestock sector.